2014
DOI: 10.3109/17483107.2014.961178
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of optic nerve prostheses

Abstract: A number of projects exist that are investigating the ability to restore visual percepts for individuals who are blind through a visual prosthesis. While many projects have reported the results from a technical basis, very little exists in the professional literature on the human experience of visual implant technology. The current study uses an ethnographic methodological approach to document the experiences of the research participants and study personnel of a optic nerve vision prosthesis project in Brussel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…A composite self-image of being a pioneer, being first, exploring the unknown, or even achieving a sciencefiction-like persona may attract some to experimentation. Kilgore and colleagues 164 reported this influence for recipients of spinal cord implants, and Lane et al [158][159][160] found similar trends for recipients of visual prostheses. A danger of relying upon adventurism as a qualifying motivation for trial participation is that risks, most of which are known to the researchers and, it is hoped, conveyed appropriately to potential participants, can be too easily dismissed by accepting the principles of autonomy and self-determination as overriding compensations.…”
Section: Restoration Of Visionmentioning
confidence: 87%
See 2 more Smart Citations
“…A composite self-image of being a pioneer, being first, exploring the unknown, or even achieving a sciencefiction-like persona may attract some to experimentation. Kilgore and colleagues 164 reported this influence for recipients of spinal cord implants, and Lane et al [158][159][160] found similar trends for recipients of visual prostheses. A danger of relying upon adventurism as a qualifying motivation for trial participation is that risks, most of which are known to the researchers and, it is hoped, conveyed appropriately to potential participants, can be too easily dismissed by accepting the principles of autonomy and self-determination as overriding compensations.…”
Section: Restoration Of Visionmentioning
confidence: 87%
“…Too often forms and protocols developed for the informed consent process appear to provide more protection to the sponsoring institution than to the volunteer. 157,158…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Images are typically processed by an externally-worn computer which instructs the implanted system to deliver electrical impulses via implanted electrodes (Brandli et al, 2016 ). Various stimulation sites have been considered: the visual cortex (Lewis and Rosenfeld, 2016 ), the optic nerve (Lane et al, 2016 ), the lateral geniculate nucleus (Nguyen et al, 2016 ) and the retina (da Cruz et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Lane et al identified a number of key personality traits that relate to motivation to participate in a visual prosthesis clinical trial, including altruism, adventurism, and advanced decision‐making skills . While these are undoubtedly useful considerations when screening for potential implant recipients, this current understanding is limited to findings from focus groups and interviews.…”
mentioning
confidence: 99%